Venovenous bypass in adult liver transplant recipients: A single-center observational case series. - Laurence Weinberg; Rebecca Caragata; Riley Hazard; Jarryd Ludski; Dong-Kyu Lee; Hugh Slifirski; Patrick Nugraha; Daniel Do; Wendell Zhang; Robert Nicolae; Peter Kaldas; Michael A Fink; et al. (PLoS ONE, 2024)
Background Very little information is currently available on the use and outcomes of venovenous bypass (VVB) in liver transplantation (LT) in adults in Australia. In this study, we explored the indications, intraoperative course, and postoperative outcomes of patients who underwent VVB in a high-volume LT unit. Methods The study was a single-center, retrospective observational case series of adult patients who underwent VVB during LT at Austin Health in Melbourne, Australia between March 2008 and March 2022. Information on baseline preoperative status and intraoperative variables, including specific VVB characteristics as well as postoperative and VVB-related complications was collected. The lengths of intensive care unit and hospital stays as well as intraoperative and in-hospital mortality were recorded. Results Of the 900 LTs performed at this center during the aforementioned 14-year period, 27 (3%) included a VVB procedure. VVB was performed electively in 16 of these 27 patients (59.3%) and as a rescue technique to control massive bleeding in the other 11 (40.1%). The median (interquartile range [IQR]) age of those who underwent VVB procedures was 48 (39-55) years; the median age was 56 (47-62) years in the non-VVB group (p<0.0001). The median model for end-stage liver disease (MELD) scores were similar between the two patient groups. Complete blood data was available for 622 non-VVB patients. Twenty-six VVB (96.3%) and 603 non-VVB (96.9%) patients required intraoperative blood transfusions. The median (IQR) number of units of packed red blood cells transfused was 7 (4.8-12.5) units in the VVB group compared to 3.0 units (1.0-6.0) in the non-VVB group (p<0.0001). Inpatient mortality was 18.5% and 1.1% for the VVB and non-VVB groups, respectively (p<0.0001). There were no significant differences in length of hospital stay or incidence of acute kidney injury, primary graft dysfunction, or long-term graft failure between the two groups. Patients in the VVB group experienced a higher rate of postoperative non-anastomotic biliary stricture compared to patients in the non-VVB group (33% and 7.9%, respectively; p = 0.0003). Conclusions VVB continues to play a vital role in LT. This case series highlights the heightened risk of major complications linked to VVB. However, the global transition to selective use of VVB underscores the urgent need for collaborative multi-center studies designed to address outstanding questions and parameters related to the safe implementation of this procedure.